Economic Globalisation and Inclusive Green Growth in Africa: Contingencies and Policy-Relevant Thresholds of Governance - Isaac K. Ofori; Francesco Figari (Sustainable Development, 2022)
This study employs macrodata for 23 African countries to examine whether good governance interacts with economic globalisation (EG) to foster inclusive green growth (IGG). First, the study finds that EG hampers IGG in Africa. Second, although unconditionally good governance promotes IGG, only government effectiveness interacts with EG to foster IGG. Across the social and environmental sustainability dimensions of IGG, however, the effects differ substantially. Notably, while the EG-governance pathways yield remarkable environmental sustainability net gains, a modest harmful effect was observed for socioeconomic sustainability. Evidence from our threshold analyses also suggests that while government effectiveness is critical for propelling EG to promote IGG, across the social and environmental perspectives of IGG, it is investments in building frameworks and structures for corruption control and the rule of law that are crucial. Our results shed new light on IGG and have several implications for Agenda 2030 and Agenda 2063.
Keywords: F18; F4; F6; F63; F64; H1; O55; Q01; Q56; 330; Africa; Economic Globalisation; Governance; Inclusive Growth; Inclusive Green Growth; Greenhouse Gas Emissions; Sustainable Development